MULTI-CHANNEL VOLUME SPHYGMOGRAPHY IN CARDIOANGIOLOGICAL SCREENING OF THE ADULT POPULATION - R. A. Khokhlov; N. I. Ostroushko; A. E. Gaydashev; D. V. Kirsanov; N. M. Akhmedzhanov (Столичная издательская компания, 2015)
Aim. To study the possibilities of using multi-channel volume sphygmography (MCVS) in prophylactic medical examination of the population. Material and methods. Simultaneous examination of 522 individuals older than 18 years was performed. Along with standard procedures provided by the prophylactic medical examination program synchronous registration of blood pressure (BP) on four extremities by MCVS was performed. At that a difference in systolic BP between arms (ΔSBParm) and legs (ΔSBPleg) and ankle-brachial index (ABI) were automatically calculated. Values of │ΔSBParm│ or │ΔSBPleg│≥15 mm Hg or ABI≤0.9 were considered as markers of atherosclerotic vascular disease. Results. Signs of peripheral arterial atherosclerotic lesions among patients ≥40 years old were found in 14.7% of the cases (95% confidence interval [CI] 11.7-18.4). Relative risks of atherosclerotic lesions in arteries increase 1.71-fold (95% CI 1.06-2.74) in arterial hypertension, 1.70-fold (95% CI 1.08-2.68) - in obesity, 1.91 fold (95% CI 1.17-3.12) - in diabetes, as well as with the increasing levels of cardiovascular risk. In patients with ischemic heart disease and a history of cerebral stroke MCVS can detect signs of multifocal atherosclerosis in 21% (95% CI 14-32) and 22% (95% CI 9-46) of the cases, respectively. Conclusion. MCVS with the determination of ΔSBParm, ΔSBPleg and ABI may be regarded as the basis for low-cost and efficient system of cardioangiological screening.